Optimization of millet (Penissetum glaucum) seed processing using a gravity table - Panozzo, Luis Eduardo; Spinelli, Victor Mouzinho; Magano, Deivid Araújo; Dörr, Caio Sippel; Panozzo, Luciana Pinto (Revista em Agronegócio e Meio Ambiente, 2024)
Millet (Pennisetum americanum) is a species cultivated for multiple purposes that presents high adaptability to different growing environments. The frequent occurrence of low quality seed lots is one of the limiting factors for this crop. Thus, the objective of this work was to evaluate the physical and physiological quality of millet seeds processed by gravity table. A batch of millet seeds (cultivar BRS 1501) was processed on a triangular gravity table. Samples were collected at different points along the equipment discharge zone (upper, upper middle, lower intermediate and disposal sections) and in the feed silo (initial batch). After processing and collection, the physical and physiological quality of the seed samples was evaluated. The results showed that the processing of millet seeds by gravity table separates the seeds by density/weight, with the heavier ones generally being of better physiological quality, facilitating the separation of batches with different quality, resulting in efficient seed separation of different sizes and weights. The processing of millet seeds by gravity table improves the physical and physiological quality of seed lots.